Mutations in a TGF-β ligand, TGFB3, cause syndromicaortic aneurysms and dissections - Bertoli-Avella, Aida M.; Evers, Christina (Journal of the American College of Cardiology, 2015)
Background - Aneurysms affecting the aorta are a common condition associated with high mortality as a result of aortic dissection or rupture. Investigations of the pathogenic mechanisms involved in syndromic types of thoracic aortic aneurysms, such as Marfan and Loeys-Dietz syndromes, have revealed an important contribution of disturbed transforming growth factor (TGF)-β signaling. - Objectives - This study sought to discover a novel gene causing syndromic aortic aneurysms in order to unravel the underlying pathogenesis. - Methods - We combined genome-wide linkage analysis, exome sequencing, and candidate gene Sanger sequencing in a total of 470 index cases with thoracic aortic aneurysms. Extensive cardiological examination, including physical examination, electrocardiography, and transthoracic echocardiography was performed. In adults, imaging of the entire aorta using computed tomography or magnetic resonance imaging was done. - Results - Here, we report on 43 patients from 11 families with syndromic presentations of aortic aneurysms caused by TGFB3 mutations. We demonstrate that TGFB3 mutations are associated with significant cardiovascular involvement, including thoracic/abdominal aortic aneurysm and dissection, and mitral valve disease. Other systemic features overlap clinically with Loeys-Dietz, Shprintzen-Goldberg, and Marfan syndromes, including cleft palate, bifid uvula, skeletal overgrowth, cervical spine instability and clubfoot deformity. In line with previous observations in aortic wall tissues of patients with mutations in effectors of TGF-β signaling (TGFBR1/2, SMAD3, and TGFB2), we confirm a paradoxical up-regulation of both canonical and noncanonical TGF-β signaling in association with up-regulation of the expression of TGF-β ligands. - Conclusions - Our findings emphasize the broad clinical variability associated with TGFB3 mutations and highlight the importance of early recognition of the disease because of high cardiovascular risk.
Gesehen am 22.05.2020